2020
DOI: 10.1007/s10694-020-00981-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fireground Exposure Simulator (FES) Prop for PPE Testing and Evaluation

Abstract: Research on the performance of personal protective equipment (PPE) for the Fire Service is challenged by the ability to repeatedly and feasibly test new designs, interventions and wear trials in realistic conditions that appropriately simulate end use environments. To support firefighter PPE research and firefighter PPE acclimation/training, a multidisciplinary team has developed a low cost, easily replicable approach for simulating conditions commonly encountered by firefighters operating on the interior of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…The Fireground Exposure Simulator (FES) has been described in detail elsewhere [17]. Briefly, the FES prop was developed based on a 2.4 m wide, 2.9 m tall and 12.2 m long intermodal shipping container divided into three sections.…”
Section: Exposure Protocolsmentioning
confidence: 99%
“…The Fireground Exposure Simulator (FES) has been described in detail elsewhere [17]. Briefly, the FES prop was developed based on a 2.4 m wide, 2.9 m tall and 12.2 m long intermodal shipping container divided into three sections.…”
Section: Exposure Protocolsmentioning
confidence: 99%
“…Temporal and spatial variability in combustion products is expected within the FES chambers, as seen by the range in median PAH air concentrations between trials (70,700À285,500 mg/m 3 ). This known variability in test conditions is similar to that measured during simulated residential fires and can be both a benefit and a limitation of the technique (Horn et al 2020). Ambient chamber air samples were used in an effort to account for this temporal variability, although it is possible that there was a saturation effect for PAHs at higher concentrations.…”
Section: Discussionmentioning
confidence: 78%
“…The ambient chamber PAH air concentrations in this study (range in medians: 70,700À285,500 mg/m 3 ) were generally higher than levels reported in our previous residential fire and training fire studies 0.017 0.003 0.008 A To estimate the impact of repeated exposure and laundering on PPE protection factors, we calculated the ratio of median ambient chamber air benzene concentrations (Table 1) to benzene under jackets (rib region) B p-value from multiple linear regression of the log-transformed ratios of benzene under jackets in the chest region to median ambient chamber air benzene concentrations by type of jacket closure, controlling for cleaning cycles/exposure trial C p-value from multiple linear regression of the log-transformed ratios vs. cleaning cycles/exposure trial, controlling for type of jacket closure (maximum 78,200 mg/m 3 ) (Fent et al 2018(Fent et al , 2019. This relative increase in concentration may provide a high-concentration challenge to identify possible leakage paths in the PPE, which is similar to traditional laboratory simulant tests (Horn et al 2020). While it is likely that the magnitude of particle penetration (mass flux) is related to the ambient chamber air concentration (and hence the rationale for expressing results as PAH ratios in this manuscript), it is also possible that this pathway could become saturated, whereby higher ambient concentrations may not necessarily translate into higher flux.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations